Targeted screening for third-generation cephalosporin-resistant Enterobacteriaceae carriage among patients admitted to intensive care units: a quasi-experimental study - Dananché, Cédric (Crit Care, 2015)
INTRODUCTION: Identification of third-generation, cephalosporin-resistant Enterobacteriaceae (3GC-RE) carriers by rectal screening at admission seems to be an important step in the prevention of transmission and outbreaks; however, little is known about its effectiveness. The aim of this study was to evaluate the impact of ‘targeted screening’ at patient admission to intensive care units (ICUs) on the incidence of 3GC-RE hospital-acquired infections (HAIs) and compare it to ‘universal screening’. METHODS: We undertook a quasi-experimental study of two ICUs (unit A: intervention group; unit B: control group) at a university-affiliated hospital between 1 January 2008 and 31 December 2011. In unit A, patients were screened universally for 3GC-RE at admission during period 1 (1 January 2008 through 30 September 2010). During period 2 (2011 calendar year), the intervention was implemented in unit A; patients transferred from another unit or hospital were screened selectively. In unit B, all patients were screened throughout periods 1 and 2. 3GC-RE-related HAI incidence rates were expressed per 1,000 patient-days. Incidence rate ratios (IRRs) were examined by multivariate Poisson regression modelling. RESULTS: In unit A, 3GC-RE-related HAI incidence rates decreased from 5.4 (95% confidence interval (CI), 4.1 to 7.0) during period 1 to 1.3 (95% CI, 0.5 to 2.9) during period 2 (P < 0.001). No changes were observed in unit B between periods 1 and 2 (P = 0.5). In unit A, the adjusted incidence of 3GC-RE-related HAIs decreased in period 2 compared with period 1 (adjusted IRR, 0.3; 95% CI, 0.1 to 0.9; P = 0.03) independently of temporal trend, trauma and age. No changes were seen in unit B (P = 0.4). The total number of rectal swabs taken showed an 85% decrease in unit A between period 1 and 2 (P < 0.001). CONCLUSIONS: Targeted screening of 3GC-RE carriers at ICU admission was not associated with an increase in 3GC-RE-related HAI incidence compared with universal screening. Total number of rectal swabs decreased significantly. These findings suggest that targeted screening may be worth assessing as an alternative to universal screening.